Analisis Teks Respon Otomatis Chatbot Provider Internet dan Telepon Seluler Menggunakan Karakter Perempuan - Arsyadin, Andika (Jurnal Pewarta Indonesia, 2025)
Customer service from various providers now integrates artificial intelligence, allowing users to access assistance anytime, 24/7. This study explores human-machine interaction through the lens of the Media Equation theory. The primary focus is to analyze the message content from three AI-powered virtual assistants: Maira from MyRepublic, Veronika from Telkomsel, and Maya from XLCare. Using a qualitative approach, this research examines text-based conversations between users and chatbots to understand how these AI systems engage with customers. The findings reveal that the chatbots, personified with female identities Maira, Veronika, and Maya are designed to exhibit human-like characteristics, making interactions feel more natural. This study highlights how human communication with AI can mirror interpersonal relationships. However, further research is needed to explore how chatbot-driven interactions align with the Media Equation theory, particularly in measuring user satisfaction.